PENGARUH PENERAPAN ETIKA BISNIS SYARIAH TERHADAP KEBERLANJUTAN USAHA : STUDI PADA UMKM DI SURABAYA - Pratiwi, Della Rista; Rosadi, Danang; Nadira, Danish Izza; Syahirah, Davelinda (Jurnal Ekonomika dan Bisnis Islam, 2023)
Business ethics includes establishing moral principles and behavior that business professionals are expected to adhere to. Business ethics plays an important role in creating a fair and transparent business environment for small and medium enterprises (SMEs), which in turn increases customer trust in the products and services offered. This research aims to analyze the concepts and principles of sharia business ethics, identify sharia business practices in SMEs, and measure the impact of implementing sharia business ethics on business sustainability in Surabaya. The method used is a mixed method which combines quantitative and qualitative approaches. The population in this research is SMEs in the city of Surabaya that meet the criteria for running a business according to sharia business ethics, with a sample of 100 sharia SMEs and interviews with 5 sharia SMEs in Surabaya. The research results show that the application of sharia business ethics contributes positively to business sustainability in SMEs in Surabaya, with increased customer trust and more harmonious business relationships. In addition, it was found that SMEs that adopt sharia principles tend to have a better reputation in the eyes of customers. However, this research also found limitations in terms of resources and knowledge regarding sharia business ethics, which could be an obstacle in implementing these principles. The implication of this research is that training and education related to sharia business ethics needs to be improved, especially for newly established SMEs.